Topological rainbow trapping based on gradual valley photonic crystals - Wang, Xinyue; Zhao, Wen; Elshahat, Sayed; Lu, Cuicui (Frontiers in Physics, 2023)
Valley photonic crystals (PCs) play a crucial role in controlling light flow and realizing robust nanophotonic devices. Here, rotated gradient valley PCs are proposed to realize topological rainbow trapping. Topological rainbow is observed despite the presence of pillars of different shapes, which indicates the remarkable universality of the design. Then, the loss is introduced to explore the topological rainbow trapping of the non-Hermitian valley PC. For the step-angle structure, the same or different losses can be applied, which does not affect the formed topological rainbow trapping. For single angle structure, the applied progressive loss can also achieve rainbow trapping. The rainbow is robust and topologically protected in both Hermitian and non-Hermitian cases, which is confirmed by the introduction of perturbations and defects. The proposed method in the current study presents an intriguing step for light control and potential applications in optical buffering and frequency routing.